2012
DOI: 10.1146/annurev.neuro.051508.135728
|View full text |Cite
|
Sign up to set email alerts
|

Under Pressure: Cellular and Molecular Responses During Glaucoma, a Common Neurodegeneration with Axonopathy

Abstract: Glaucoma is a complex neurodegenerative disorder that is expected to affect 80 million people by the end of this decade. Retinal ganglion cells (RGCs) are the most affected cell type and progressively degenerate over the course of the disease. RGC axons exit the eye and enter the optic nerve by passing through the optic nerve head (ONH). The ONH is an important site of initial damage in glaucoma. Higher intraocular pressure (IOP) is an important risk factor for glaucoma, but the molecular links between elevate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
236
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 288 publications
(238 citation statements)
references
References 164 publications
1
236
0
1
Order By: Relevance
“…RGC death is involved in several retinal diseases such as glaucoma and optic ischemia, which often lead to vision loss and even blindness (59,60). Much effort has been undertaken to produce RGCs for cell-based therapies directly in vitro from various stem cells (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…RGC death is involved in several retinal diseases such as glaucoma and optic ischemia, which often lead to vision loss and even blindness (59,60). Much effort has been undertaken to produce RGCs for cell-based therapies directly in vitro from various stem cells (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…To understand the molecular responses occurring during glaucoma, gene expression profiles of human lamina astrocytes and ONH tissue from animal models have been studied (reviewed in refs. 2,15,23). These studies identified changes in multiple genes/pathways related to immune responses, as well as structural and inflammatory changes in the ONH (8,24,25).…”
mentioning
confidence: 99%
“…glaucoma | astrocytes | complement | EGFR | WLDS G laucoma is a common disorder characterized by the loss of retinal ganglion cells (RGCs) and degeneration of the optic nerve (1)(2)(3). Intraocular pressure (IOP) elevation is a major risk factor for developing glaucoma (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 The primary treatment goal is to reduce intraocular pressure (IOP), which is a risk factor for worsening of glaucoma-related neuropathy and axonal damage leading to vision loss. [3][4][5] Successful treatment for glaucoma is linked with good compliance/adherence, 6 yet many patients with glaucoma, especially those without symptoms, require multiple medications for adequate IOP control and this requirement may lead to compliance problems and consequently reduced efficacy.…”
mentioning
confidence: 99%